Associations between metabolic syndrome at index PCI and 1-year outcomes. (14th October 2021) - Chandrasekhar, J; Chowdhury, E; Eccleston, D; Delacroix, S; Worthley, S
Abstract: Background: The prevalence of obesity, diabetes and metabolic syndrome is rising, with negative health consequences for the community. Purpose: We sought to examine the prevalence and impact of metabolic syndrome (MetS) on 1-year outcomes from an Australian cohort of all-comer PCI patients. Methods: We retrospectively analysed the GenesisCare Outcomes multicentre Registry of prospectively collected data in patients undergoing PCI from 2008–2020. Metabolic syndrome was defined as presence of any 3 features including hypertension, diabetes, obesity with body mass index ≥30 kg/m 2 and dyslipidaemia. We examined 1-year outcomes for death and MACE (death, MI or TLR), and the adjusted risk after accounting for each of the defining variables. Results: During the study period from 2005–2018, 14, 405 were included, of which 5480 (38%) had metabolic syndrome. MetS patients were somewhat younger without sex differences (∼76% men). They had greater prevalence of defining characteristics, and smoking and lower prevalence of myocardial infarction presentation compared to non-MetS patients. MetS patients had higher prevalence of B2/C type lesions, restenosis, chronic total occlusions and multivessel disease. At 30-days MetS patients had lower risk of re-infarction (0.1% vs. 0.3%, p=0.011) but from 30-days to 1-year they had greater risk of MI (1.1% vs. 0.5%, p<0.01), TLR (1.5% vs. 1.1%, p=0.03), readmissions (21.8% vs. 19.8%, p=0.008) and MACE (3.6% vs. 2.7%, p=0.03) without differences in mortality (1.3% in both, p=0.88). Unadjusted models showed trend for greater risk of 1-year MACE with MetS, HR 1.15 (95% CI 1.00–1.33), p=0.054. In multivariable models, this risk was lost after adjusting individually for hypertension, dyslipidaemia and insulin-treated diabetes, but not after adjustment for obesity and non-insulin diabetes (See Figure). Conclusions: Metabolic syndrome was noted in over one-third of all-comer PCI patients, and was associated with greater risk of 1-year MACE. This risk appeared to be related to hypertension, dyslipidaemia and insulin-treated diabetes but not obesity. FUNDunding Acknowledgement: Type of funding sources: None.